Where Shall We Go?. Issue 5 (September 2016) - Kaebnick, Gregory E.
Abstract: This issue of the Hastings Center Report coincides with the annual conference of the American Society for Bioethics and Humanities, whose theme this year is "Where do we stand?" The issue addresses that theme with the article by Debra Mathews and colleagues and the set of brief response essays that follow it. Mathews et al., drawing on work carried out by the Association of Bioethics Program Directors, pose questions about how to understand and evaluate the worth of bioethics research. Those questions require them to think very broadly about what bioethics is, in the first place, and how it is related to medicine, health policy, science, and society generally. In short, they are thinking at the highest level about the question, where do we stand?